(untitled) (Південний архів (історичні науки), 2022)
Purpose. The study of social-economic development of the South of modern Ukraine requires an analysis of various branches of economic activity. Considering predominantly agricultural form of activity of the settlements of Odessa district, the analysis of economic development is an important aspect in the study of the general economic situation in the region. The key part of studying Kherson province and Odessa county zemstvos is the detailed research of their activity, one of them being the struggle with the effects of bad harvest in the county in the 1870s. The analysis of statistical works and available archival sources on the outlined subject will allow covering the situation of the population in the outlined period in detail. Methods. The research is based on source studies methods for identifying, analyzing and evaluating sources. The method of historical research is used to identify the range of archival and statistical sources necessary to cover the topic of the article. Results. The research on the activities of zemstvos existing in the South of Ukraine allows us to conclude about the active work of local governments in overcoming the consequences of crop failures in the Odessa district in the 70’s of the XIX century. The analysis of statistical data collected by the Odessa County Administration and archival documents allowed us to analyze the main aspects of local government activity in the elimination of the consequences of crop failures of the 70’s of the XIX century. The data presented in the article allow us to trace the formation of changes in the system of providing the population of the county with money and grain loans. The process of formation of the principle of distribution of loans among the settlements is represented. The aspect of providing assistance to various groups of population, including the clergy, is highlighted. One of the aspects represented in the article is the charitable activities of the Kherson governor and others in the fight against the consequences of crop failures. Conclusions. The consequences of crop failures for the population in economic and financial aspects, both for privately owned peasants and for former foreign colonists, are analyzed. The main agricultural crops grown by the population and the influence of crop capacity of each of them on the economic situation are determined.